The Effect Of Financial Performance Ratio On Probability Of Sharia National Retirement Savings Banks (BTPN) - Kinasih, Eti; Thoyib, Alhadi Kurnia (Al-Mashrof: Islamic Banking and Finance, 2024)
This study aims to analyze the effect of Return On Assets (ROA) on Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (BOPO) and Financing To Deposit Ratio (FDR) at Bank BTPN Syariah for the 2013-2022 period. The method used in this study is multiple linear regression analysis method and data processed using SPSS 25 program. The population in Bank BTPN Syariah's financial statement research and the sample in this study is the entire population in the financial statement study from 2013-2022. The results showed that the CAR at Bank BTPN Syariah had a negative and significant effect on ROA with a coefficient value of -0.129 and a significance value of 0.001. BOPO at Bank BTPN Syariah has a negative and significant effect on ROA with a coefficient value of -0.386 and a significance value of 0.000. FDR at Bank BTPN Syariah has a positive and significant effect on ROA with a coefficient value of 0.081 and a significance value of 0.007. Simultaneously, CAR, BOPO and FDR at Bank BTPN Syariah have a significant effect on ROA with a significance value of 0.000. Test coefficient of determination (R2) of 99.8% which shows that the dependent variable (ROA) can be influenced by independent variables (CAR, BOPO and FDR) while the remaining 0.2% is influenced by other factors.